Penerapan Internet Of Things (IoT) Pada Sistem Monitoring Penggunaan Air PDAM Rumah Tangga - Indra Gunawan; Muhammad Wasil; Mahpuz Mahpuz (Infotek: Jurnal Informatika dan Teknologi, 2023)
Water is a source of life that is needed by living things. Many people have switched to using PDAM water to fulfill their daily water needs so in the distribution process the PDAM requires a process of checking or recording by officials the amount of water used that is distributed to each customer. This raises a problem, namely that there is often a discrepancy between the amount of water used and the fees that must be paid and the water meters used by the PDAM are still analog in nature so the water usage data is difficult for customers to know. This is one of the factors causing the soaring bills of fees that must be paid for water needs to the PDAM every month which often results in several possibilities, namely non-payment, leaks, or fraud. So we need a tool to facilitate the PDAM and PDAM water customers in monitoring water use as well as the amount of payment. The tool is in the form of a PDAM Water Usage Monitoring System Design using Internet of Things technology using a water flow sensor that will detect the use of water used, RTC to determine a date and time in the BLYNK application display, processed via the ESP32 Node MCU and displayed on the LCD as the output of current usage and bills to be paid. The processed data results will be sent to the BLYNK web server and can be viewed through the BLYNK application on an Android smartphone. The error value from the reading of the water flow sensor is 1%, which means the accuracy level is 99%. Meanwhile, the data from the reading of the system for calculating the cost of using PDAM water does not contain errors so the accuracy of the data reaches 100%.